Effects of plant alkaloids on mitochondrial bioenergetic parameters. (August 2021) - Patalas-Krawczyk, Paulina; Malinska, Dominika; Walczak, Jaroslaw; Kratzer, Gilles; Prill, Monika; Michalska, Bernadeta; Drabik, Karolina; Titz, Bjorn; Eb-Levadoux, Yvan; Schneider, Thomas; Szymanski, Jedrzej; Hoeng, Julia; et al.
Abstract: Mitochondria are among the first responders to various stress factors that challenge cell and tissue homeostasis. Various plant alkaloids have been investigated for their capacity to modulate mitochondrial activities. In this study, we used isolated mitochondria from mouse brain and liver tissues to assess nicotine, anatabine and anabasine, three alkaloids found in tobacco plant, for potential modulatory activity on mitochondrial bioenergetics parameters. All alkaloids decreased basal oxygen consumption of mouse brain mitochondria in a dose-dependent manner without any effect on the ADP-stimulated respiration. None of the alkaloids, at 1 nM or 1.25 μM concentrations, influenced the maximal rate of swelling of brain mitochondria. In contrast to brain mitochondria, 1.25 μM anatabine, anabasine and nicotine increased maximal rate of swelling of liver mitochondria suggesting a toxic effect. Only at 1 mM concentration, anatabine slowed down the maximal rate of Ca 2+ -induced swelling and increased the time needed to reach the maximal rate of swelling. The observed mitochondrial bioenergetic effects are probably mediated through a pathway independent of nicotinic acetylcholine receptors, as quantitative proteomic analysis could not confirm their expression in pure mitochondrial fractions isolated from mouse brain tissue. Highlights: Anatabine is a modulator of the mPTP in mouse brain and liver mitochondria. Nicotine, anatabine and anabasine at various concentrations affect mouse brain mitochondrial parameters. The observed effects on OXPHOS and mPTP is not mediated by nicotinic acetylcholine receptors in isolated mitochondria.